Analyzing Bulk Flow Characteristics of Debris Flows Using Their High Frequency Seismic Signature. Issue 12 (24th December 2021) - Zhang, Zhen; Walter, Fabian; McArdell, Brian W.; de Haas, Tjalling; Wenner, Michaela; Chmiel, Małgorzata; He, Siming
Abstract: Quantifying debris‐flow characteristics remains a key challenge in natural hazard research. Recent studies suggest that seismic signals can reveal debris‐flow properties. However, the accuracy and applicability of theoretical models linking bulk flow properties to the seismic signature of a debris flow remain elusive. By extending a previously proposed model of random single‐particle impact forces to multi‐particle force chains acting on the channel bed, we describe the generation of high frequency seismic signals, and thereby estimate the bulk flow dynamics of six debris‐flow events at Illgraben, Switzerland. The theoretically predicted basal force fluctuations agree with in‐situ measurements at a basal force plate and seismic signals recorded adjacent to the channel. According to our model, both random single‐particle impacts and random impacts caused by multi‐particle force chains control basal force fluctuations. The relative contributions of single particles and of multi‐particle force chains may vary significantly for different events and different positions within events. The relative contribution of multi‐particle force chains is expected to be larger in the flow front, where particle concentrations are higher. The ratio between single‐particle and multi‐particle contributions appears to control the non‐linear relation between flow depth and the magnitude of the high frequency seismic signals. Our results suggest that fluctuating basal forces are strongly controlled by particle size and flow depth, and open new perspectives for the understanding of bulk flow characteristics, such as flow depth and weight, and of the high frequency seismic signals generated by debris flows. Plain Language Summary: Traditional methods have many limitations in observing and estimating debris‐flow characteristics, such as flow depth and weight. Although an increasing number of studies has recently shown the potential of using seismic signals to observe these debris‐flow characteristics, the physical relation between these characteristics and ground vibrations is not well understood. Here we develop a model, which describes how particles within a debris flow transmit forces as they collide with the ground. We focus on six debris flows at Illgraben, Switzerland, and observe a good agreement between modeled and measured forces. We find that both multi‐particle force chain impacts and single‐particle impacts control the debris‐flow basal force fluctuations. Thicker flows transmit more seismic energy to the underlying ground. Our study shows how seismic measurements can be used to obtain quantitative information about debris flows. Key Points: We extend the single‐particle impact model to multi‐particle force chains generating debris‐flow seismic signals Theoretically predicted basal force fluctuations are consistent with in‐situ measurements and inverted results from seismic signals Both single‐particle impacts and multi‐particle force chain impacts control basal force fluctuations